Estimating the health workforce requirements and costing to reach 70% COVID-19 vaccination coverage by mid-2022: a modelling study and global estimates. Issue 8 (5th August 2022) - Boniol, Mathieu; Siyam, Amani; Desai, Shalini; Gurung, Santosh; Mirelman, Andrew; Nair, Tapas Sadasivan; Diallo, Khassoum; Campbell, James
Abstract : Objectives: The implementation of COVID-19 vaccination globally poses unprecedented stress to health systems particularly for countries with persisting health workforce shortages prior the pandemic. The present paper estimates the workforce requirement to reach 70% COVID-19 vaccination coverage in all countries by mid-2022 using service target–based estimation. Methods: Health workforce data from National Health Workforce Accounts and vaccination coverage reported to WHO as of January 2022 were used. Workload parameters were used to estimate the number of health workers needed with a service target–based approach, the gap and the scale-up required partially accounting for countries' challenges, as well as the associated costs in human resources. Results: As of 1 January 2022, only 34 countries achieved 70% COVID-19 vaccination coverage and 61 countries covered less than a quarter of their population. This analysis showed that 1 831 000 health workers working full time would be needed to reach a global coverage of 70% COVID-19 vaccination by mid-2022. To avoid severe disruptions to health system, 744 000 additional health workers should be added to domestic resources mostly (77%) in low-income countries. In a sensitivity analysis, allowing for vaccination over 12 months instead of 6 months would decrease the scale-up to 476 000 health workers. The costing for the employment of these 744 000 additional health workers is estimated to be US$2.5 billion. In addition to such a massive scale-up, it is estimated that 29 countries would have needed to redeploy more than 20% of their domestic workforce, placing them at serious risk of not achieving the mid-year target. Conclusion: Reaching 70% global coverage with COVID-19 vaccination by mid-2022 requires extraordinary efforts not before witnessed in the history of immunisation programmes. COVID-19 vaccination programmes should receive rapid and sustainable investment in health workforce.